Ethics and HRD: A New Approach to Leading Responsible Organizationsby HatcherTim. Cambridge, MA: Perseus, 2002. - Krefting, Linda A. (Academy of Management Review, 2003)
The article presents a review of the book ?Ethics and HRD: A New Approach to Leading Responsible Organizations,? by Tim Hatcher.